2011
DOI: 10.1109/tbme.2011.2166398
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Parameter Identification in Models of Respiratory Mechanics

Abstract: Potential harmful effects of ventilation therapy could be reduced by model-based predictions of the effects of ventilator settings to the patient. To obtain optimal predictions, the model has to be individualized based on patients' data. Given a nonlinear model, the result of parameter identification using iterative numerical methods depends on initial estimates. In this work, a feasible hierarchical identification process is proposed and compared to the commonly implemented direct approach with randomized ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…While numerical integration coupled with gradient based identification methods are frequently used successfully (Sundaresan et al 2009;Schranz et al 2011), it is important to know the limitations of such methods. In particular, this investigation has shown that numerical integration methods which handle discontinuities poorly, such as the proprietary MATLABTM methods, are likely to cause parameter identification failure when poorly applied.…”
Section: Discussionmentioning
confidence: 99%
“…While numerical integration coupled with gradient based identification methods are frequently used successfully (Sundaresan et al 2009;Schranz et al 2011), it is important to know the limitations of such methods. In particular, this investigation has shown that numerical integration methods which handle discontinuities poorly, such as the proprietary MATLABTM methods, are likely to cause parameter identification failure when poorly applied.…”
Section: Discussionmentioning
confidence: 99%
“…The initial values for t s and t f are determined by fitting the conventional single compartment lung model using a hierarchical approach [10]. The fitted model will have regions where the modelled pressure is lower than the pressure data.…”
Section: A Initial Value Selectionmentioning
confidence: 99%
“…Accurate initial parameter values can significantly reduce the incidence of finding local minima. Thus, a hierarchical parameter identification process is applied (Schranz et al, 2011).…”
Section: Parameter Identificationmentioning
confidence: 99%
“…The hierarchical method provides patient-specific initial values by identifying simpler models with fewer variable parameters first (Schranz et al, 2011). These first results provide appropriate initial values for the identification of the next, more complex model.…”
Section: Parameter Identificationmentioning
confidence: 99%